Structural indicators for inclusive systems in and around schools : analytical report. - Downes, Paul; Nairz-Wirth, Erna; Rusinaitè, Viktorija (Conseil de l'Europe, 2017)
International evidence indicates that school systems need to change in order to tackle early school leaving and improve social inclusion in education and society. Policy-makers and school actors require practical tools to assist them in this process, made all the more urgent by the EU2020 headline target to reduce early school leaving. This report develops such practical tools; it is designed to inform strategic policy and practice by offering an innovative framework of structural indicators for early school leaving prevention and inclusion in school. It draws upon key European Council and Commission policy documents on early school leaving prevention, and also on the Paris Declaration 2015 on promoting common values of freedom, tolerance and non-discrimination through education, which includes a focus on social marginalization. This report expands on these key policy documents with recent international research and with the input of a number of key policy stakeholders. Inclusion in education, viewed more comprehensively as inclusive systems in and around schools, concentrates on supportive, quality learning environments, on welcoming and caring schools and classrooms, and on preventing discrimination. It addresses the needs of students in a holistic way (their emotional, physical, cognitive and social needs), and recognises their individual talents and voices. It is open to the voices and active participation of parents, and also wider multidisciplinary teams and agencies. Inclusive systems in and around schools particularly focus on the differentiated needs of marginalised and vulnerable groups, including those at risk of early school leaving and alienation from society. This proposed framework of structural indicators for inclusive system development applies to both national policy level and school level. The key overall areas examined in this report include a whole school approach to developing inclusive systems, and teacher and school leadership quality for inclusive systems in and around schools. Macrostructure issues and promotion of system integration of policy and practice are also addressed. Other key thematic areas of the report include a multidisciplinary focus on health and welfare issues in education, on promoting parental involvement and family support, and on meeting the needs of particularly vulnerable individuals and groups. These thematic chapters support the structural indicators with international evidence, combined with the EU policy documents. The structural indicators are underpinned by ten key principles for inclusive systems in and around schools, and are based on EU policy documents, legal principles and international research. These ten principles include: a System wide focus on addressing system blockages as barriers and on system supports; a Holistic approach that recognises the social, emotional and physical needs of students and not simply their academic, cognitive ones; and the principle of Equality and non-discrimination, which acknowledges that different groups may need additional supports in a respectful environment free of prejudice. The principle of Children’s voices requires a commitment to concerns directly affecting children’s own welfare, with due regard to their ages and maturity. The principle of Building on strengths challenges negative deficit labels of vulnerable groups by going beyond mere prevention and instead seeking to promote their personal and educational growth. The principle of Active participation of parents in school requires a strategic focus on marginalised parents. The principle of Differentiation acknowledges that different levels of need require different prevention strategies, including for students and families experiencing moderate risk and chronic need. The Multidisciplinarity principle recognises the need for a multifaceted response for marginalised students with complex needs; marginalised groups include those experiencing poverty and social exclusion, those at risk of early school leaving, those experiencing bullying, mental health difficulties and/or special educational needs, as well as some groups of migrants and ethnic minorities. The principle of Representation and participation of marginalised groups involves a distinct focus on processes and structures for their representation and participation. The Lifelong learning principle brings educational focus on active learning methodologies for issues of active citizenship, personal and social fulfilment, intercultural dialogue across communities, as well as on poverty and social inclusion, and employment. The framework of structural indicators for inclusive systems in and around schools is developed into two tools, one for use by national policy makers and one for use by schools. These tools can be used as verifiable self-assessment approaches, and potentially also for comparative external assessment purposes to support development of inclusive education systems across Europe. This framework of enabling conditions for school system development is a reference point for strategic decision-making. It is not a framework meant to be static and frozen in time; rather, it should be viewed as dynamic, as an enduring reference point that is subject to additions and revisions over time, both locally and nationally.